Fault Location Schemes for Complex Power Grid Based on Multidimensional Information Fusion. Issue 8 (9th May 2019) - Liang, Rui; Chi, Peng; Cheng, Menghan; Liu, Chenglei; Wang, Fei
Abstract: Fast and accurate fault location in complex power grid is crucial to ensure the safe operation of power grid. It is inevitable that fault location is not merely in single transmission line but in complex power grid. This article first describes the correlation properties of multidimensional fault characteristics in complex power grid and reveals the relationship between the multidimensional fault characteristics and the fault distance. Then the optimized clustering analysis algorithm is presented to realize rapid and accurate identification of the fault area based on the multidimensional characteristics of measuring points. All the measuring points are divided into four categories: fault area, fault boundary region, fault transition region, and nonfault region. Location zone is constructed by fault region and fault boundary region. Finally, to get fault location results and fault occurrence time, linear equations are established by correlation properties of spatiotemporal information in location zone and solved by the least square method. At the same time, the applicability and reliability of the proposed method are analyzed. The IEEE 30-Bus System and IEEE 57-Bus System are built in PSCAD/EMTDC software. Compared with the existing method, the positioning accuracy of the proposed method is improved by 70.62%. Large number of simulation results show that the proposed method of wide-area fault location has higher accuracy and adaptability.